2023
DOI: 10.1097/eja.0000000000001798
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cerebral autoregulation during step-wise increases in blood pressure during anaesthesia

Abstract: BACKGROUND Classically, cerebral autoregulation (CA) entails cerebral blood flow (CBF) remaining constant by cerebrovascular tone adapting to fluctuations in mean arterial pressure (MAP) between ∼60 and ∼150 mmHg. However, this is not an on–off mechanism; previous work has suggested that vasomotor tone is proportionally related to CA function. During propofol-based anaesthesia, there is cerebrovascular vasoconstriction, and static CA remains intact. Sevoflurane-based anaesthesia induces cerebral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 69 publications
(169 reference statements)
0
8
0
Order By: Relevance
“…The systematic literature search yielded 2586 records. After removing 703 duplicates and two retracted papers, we screened 1881 records and finally identified 45 studies that met the eligibility criteria [3, 15–58]. Four additional studies were identified through PubMed and Google Scholar searches and screening relevant articles' reference lists [59–62].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The systematic literature search yielded 2586 records. After removing 703 duplicates and two retracted papers, we screened 1881 records and finally identified 45 studies that met the eligibility criteria [3, 15–58]. Four additional studies were identified through PubMed and Google Scholar searches and screening relevant articles' reference lists [59–62].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen of the 49 eligible studies had been conducted in awake healthy subjects [15, 17, 18, 20, 30–32, 37, 39–41, 46, 47, 53, 58] and the remaining 34 studies in anaesthetised subjects [3, 16, 19, 21–29, 33–36, 38, 42–45, 48–52, 54–57, 59–62]. Among the latter, 31 involved patients undergoing various surgical procedures [3, 16, 19, 21–23, 25–29, 34–36, 38, 42–45, 48–52, 54, 55, 57, 59–62], two involved healthy volunteers [24, 33] and one involved patients with hyperdynamic sepsis or cardiac diseases [56].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations